2004
DOI: 10.1534/genetics.104.029686
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Response to Long-Term Artificial Selection for Oil Concentration in the Maize Kernel

Abstract: In one of the longest-running experiments in biology, researchers at the University of Illinois have selected for altered composition of the maize kernel since 1896. Here we use an association study to infer the genetic basis of dramatic changes that occurred in response to selection for changes in oil concentration. The study population was produced by a cross between the high-and low-selection lines at generation 70, followed by 10 generations of random mating and the derivation of 500 lines by selfing. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
162
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(190 citation statements)
references
References 27 publications
13
162
3
6
Order By: Relevance
“…The design combining large-scale diversity lines with deep RNA-seq can provide sufficient coverage of gene expression and help to narrow the eQTL to gene level, generating the hypothesis of gene regulatory relationship. The data set in this study has been successfully used in exploring the genetic architecture of oil biosynthesis and accumulation in maize kernel, which is a typical quantitative trait controlled by polygenic loci 46 . The results showed that 74 highly significantly associated loci were responsible for oil concentration and fatty acid composition 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The design combining large-scale diversity lines with deep RNA-seq can provide sufficient coverage of gene expression and help to narrow the eQTL to gene level, generating the hypothesis of gene regulatory relationship. The data set in this study has been successfully used in exploring the genetic architecture of oil biosynthesis and accumulation in maize kernel, which is a typical quantitative trait controlled by polygenic loci 46 . The results showed that 74 highly significantly associated loci were responsible for oil concentration and fatty acid composition 5 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Monsanto's breeding program uses a subset of >50 different QTLs that exist for each of the characteristics of days to silking, days to anthesis, and grain oil content (Laurie et al, 2004;Buckler et al, 2009). Additionally, there are >100 QTLs associated with the development of root architecture in maize (Zurek et al, 2015), and breeding companies screen for a targeted subset of them within their breeding pipeline.…”
Section: Technologies Used To Expedite the Breeding Processmentioning
confidence: 99%
“…These high genomic mutation rates can be explained by either a low mutation rate per locus with a very large number of loci (e.g. more than 50 in Laurie et al 2004) or a high mutation rate per locus with a moderate number of loci (of the order of 5 or 10) as found for the onset of flowering (Lande 1981;see references in Fox 2003) and other traits in plants (Kearsey & Farquhar 1998), for example due to unequal exchange in tandemly duplicated gene families ( Frankham et al 1978). The ratio of the mutational to the environmental variance was taken from Lande (1975) and Lynch (1988), while the value of the environmental variance was chosen to match previous observations for flowering time in herbaceous species (Lande 1981;O'Neil 1997;Shaw & Chang 2006 single ovule but a large number of pollen grains so that it can contribute once as female and several times as male to the next generation.…”
Section: The Modelmentioning
confidence: 99%